SHARIA FINANCIAL SYSTEM THE BEST SOLUTION FOR OVERCOMING POVERTY IN INDONESIA - Wira Irpandi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Public welfare is the goal of the Islamic financial system. People who are impoverished or experiencing poverty do not mean that they are completely lazy. However, they are people who have not had access to a better life. The Islamic financial system is the most appropriate system for overcoming poverty in Indonesia. It doesn't only need a Muslim community, but this Islamic financial system can also be used by non-Muslim communities throughout Indonesia or the world. Because the Islamic financial system does not aim to collect as much wealth as possible. But in this system we are taught how a better life can be achieved together.